Uji Aktivitas Antibakteri Ekstrak Etanol Sabut Kelapa (Cocos nucifera Linn.) Terhadap Bakteri Cutibacterium acnes - Farhah, Amelia; Mardiyanti, Siti (Universitas Gunadarma, 2024)
Cutibacterium acnes is the main bacteria that causes acne. Acne is a skin infection that is common and often complained about. Acne is an obstructive skin disease and chronic inflammation of the pilosebaceous glands, which is characterized by the appearance of comedones, papules, pustules and nodules. Treatment of acne can be done with the help of antibiotics. However, continuous use of antibiotics can cause resistance. This study aims to test the antibacterial activity by using natural ingredients, namely ethanol extract of coconut husk (Cocos nucifera L.) against Cutibacterium acnes. The study was carried out by extracting coconut husk simplicia using maceration method using 96% ethanol solvent. From the extraction results obtained, the antibacterial activity was then tested using the well diffusion method. The results obtained were that the ethanol extract of coconut husk contained tannins, flanonoids, saponins and terpenoids. The results of the antibacterial activity test showed that 7.5% coconut husk ethanol extract produced an inhibitory zone diameter of 7.05 mm, 10% extract produced an inhibitory zone diameter of 13.05 mm, and 12.5% extract produced an inhibitory zone diameter of 14 . 15 mm with strong antibacterial properties.